Odnos učiteljev francoščine do poučevanja slovnice - Cajhen, Simona (Vestnik za tuje jezike, 2014)
The present article is concerned with presenting the importance and role which is given to grammar by Slovenian teachers of the French language in secondary schools. Firstly the concept of grammar is defined and its position throughout history and in both curricula for the French language in Slovenian secondary schools is presented. Furthermore the changing role of grammar in the external exams is presented. The main part of this article is related to the presentation of the research work and its results, in which we focused mostly on the questionnaire results% presentation. On the basis of the obtained results we can assume that Slovenian teachers consider grammar as a very important element of teaching, although they make use of different approaches in their teaching in order to develop all components of communicative competence. They think that linguistic competence is only one element of communicative language competence, therefore they are rarely limited only to linguistic competence and accuracy.
Keywords: francoščina; French; tuji jeziki; poučevanje jezika; slovnica; grammar; učbeniki; srednje šole; komunikacijski pristop; mnenja učiteljev